The Treatment of A Case of Feline Panleukopenia Virus in a Mixed Persian Cat - Ahmad Syarifuddin; Jessica Anggun Safitri; Sarwo Edy Wibowo; Dedi Damhuri; Amelia Triningsih Triningsih (Journal of Applied Veterinary Science And Technology, 2025)
Background: Feline panleukopenia virus (FPV) is a highly contagious and frequently fatal disease, particularly affecting unvaccinated juvenile cats. Clinical manifestations typically include leukopenia, diarrhea, dehydration, vomiting, and depression. The disease exhibits high morbidity and mortality rates, especially in young animals without prior immunization. Purpose:  This report aims to provide clinical insight into the diagnosis and symptomatic management of FPV in domestic cats. Case: An 8-month-old unvaccinated female cat weighing 2.3 kg was presented with signs consistent with panleukopenia. The patient had not received deworming treatment and lived in a semi-outdoor environment with three other cats. Physical examination focused on the oral cavity, nasal passages, eyes, ears, and abdomen. Hematological findings supported suspicion of viral infection. The history revealed that the patient’s littermates had died after exhibiting similar symptoms. Case Management:  Therapy focused on symptomatic treatment, including the administration of broad-spectrum antibiotics (ceftriaxone) to prevent secondary bacterial infections and reduce the risk of septicemia. Gastric protection was provided using ranitidine to inhibit gastric acid secretion and prevent complications such as ulcers and esophageal erosion. Supportive management also included fluid therapy and antidiarrheal care tailored to the patient's clinical status. Conclusion: Prompt diagnosis and appropriate symptomatic management significantly influence the outcome of FPV cases. Preventive strategies, including vaccination and routine deworming, remain essential in reducing the incidence and severity of infection. This case highlights the importance of early intervention and individualized treatment in improving recovery and survival rates in cats affected by panleukopenia.